In the balance : law and politics on the Roberts Court - Tushnet, Mark V. (W. W. Norton & Company, 2013)
From off the wall and down the rabbit hole -- Making the Roberts Court -- The rookie and sophomore years -- The court of public opinion, the Supreme Court, and gun rights -- Business stooge or umpire? : business cases in the Roberts Court -- The Roberts Court -- Sticks and stones, lies and insults -- Citizens united and campaign finance.